MISI DALAM PERJANJIAN LAMA - Megawati Manullang (Institut Agama Kristen Negeri Tarutung, 2019)
AbstractGenerally, missiology can be understood as the study of the Gospel messagespreading or what is better known as Sending. Thus, this Gospel spreading isconsidered as one of the main task or function of churchestht is to share the good news about Jesus Christ worldwide. Therefore, this comprehension cannot be taken wrong, however in the Old Testament, missiology has to be seen from the standpoint on “how God the Father called and sent his servants to carry out all the tasks assigned to them in order to turn the people of Israel from their stubborness so that they could be saved and not be perished in the punishment that were bounded to them’’ In the old Testament there is an obvious assignment to do the outreach mission to all nations all around the world. The main focus in the Old Testament is the choosing of Israel and its relations to the other nations.Key words: Mission, Old Testament